"Criterios de alta política". La anexión de Chiapas a México en el canal de Tehuantepec (Tzintzun, Revista de Estudios Históricos, 2016)
Upon taking up this topic the first problem the author confronts is the lack of interest in Chiapas shown by Mexican historians. Concerning the annexation or acquisition of the Chiapas territory there prevails a nationalist focus quite contrary to the views of researchers who tend to give preference to the analysis of groups and economic interests and to the construction project of an ocean-to-ocean communication route through the isthmus of Tehuantepec. This article presents the fundamental aspects of Agustín de lturbide's Central American policy and the efforts of Tadeo Ortiz, Manuel Mier y Terán and Vicente Filisola to convince other Central American states to join Mexico and form one great nation. In the end, the initiative failed and a second stage was begun emphasizing the incorporation of Chiapas into the national territory. Toe negotiations were by no means easy, although the economic interests that the region shared with the states of Tabaso and Oaxaca had much to do with the outcome.